2014
DOI: 10.3389/fchem.2014.00098
|View full text |Cite
|
Sign up to set email alerts
|

Insights into enzymatic halogenation from computational studies

Abstract: The halogenases are a group of enzymes that have only come to the fore over the last 10 years thanks to the discovery and characterization of several novel representatives. They have revealed the fascinating variety of distinct chemical mechanisms that nature utilizes to activate halogens and introduce them into organic substrates. Computational studies using a range of approaches have already elucidated many details of the mechanisms of these enzymes, often in synergistic combination with experiment. This Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 99 publications
1
20
0
Order By: Relevance
“…Non-haem iron (NHFe) halogenases have been the focus of much attention due to their unique ability to install halogens at unreactive positions in complex substrates with exquisite chemo-and regioselectivity. The interest in biological halogenation generally has been boosted over the last decade by the discovery of several new classes and families of halogenases; the progress has been extensively reviewed, [1][2][3][4][5][6][7][8][9][10][11][12] most recently by Moore and co-workers. 12 Beyond the fundamental biosynthetic and mechanistic interest, halogenases have attracted attention as ''green'' catalysts for biotechnological and biocatalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Non-haem iron (NHFe) halogenases have been the focus of much attention due to their unique ability to install halogens at unreactive positions in complex substrates with exquisite chemo-and regioselectivity. The interest in biological halogenation generally has been boosted over the last decade by the discovery of several new classes and families of halogenases; the progress has been extensively reviewed, [1][2][3][4][5][6][7][8][9][10][11][12] most recently by Moore and co-workers. 12 Beyond the fundamental biosynthetic and mechanistic interest, halogenases have attracted attention as ''green'' catalysts for biotechnological and biocatalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Upon comparison of the halide ion binding site, an attempt was made to convert the chlorinase to a fluorinase by substituting the respective halide-binding residues. 57,66 Structural 67,68 and computational studies 69 of the fluorinase and chlorinase provided insights into the mechanism of halide selection. Crystal structures of the fluorinase in complex with chloride ion (since F − is indistinguishable from water) showed that the halide coordination is reliant on S158 and T80 in the fluorinase which are substituted with G131 and Y70 in the chlorinase, respectively (Fig.…”
Section: Fluorination Biocatalystsmentioning
confidence: 99%
“…Haloperoxidases are capable of efficiently catalysing the halogenation of a variety of organic compounds in the presence of hydrogen peroxide and halides (Cl − , Br − and I − ) . Among halogenated organic compounds, brominated ones are of particular interest due to their extensive applications in the synthesis of flame retardants, pharmaceuticals, biocides and pesticides .…”
Section: Introductionmentioning
confidence: 99%
“…Among halogenated organic compounds, brominated ones are of particular interest due to their extensive applications in the synthesis of flame retardants, pharmaceuticals, biocides and pesticides . In recent times, because of its convenient and eco‐friendly nature, oxidative bromination with bromoperoxidases and their mimics has drawn considerable attention over traditional bromination using Br 2 . Vanadium(V)‐based bromoperoxidases are most widespread among all the naturally occurring bromoperoxidases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation